The billionaire's island reunion - Meier, Susan (Meier, Susan. Billion-dollar family., 2021)
His unexpected houseguest! But is she there to stay...? In this Billion-Dollar Family story, twelve years ago, with no warning or explanation, Reese Farrell broke Cade Smith's heart. Now she's lounging by his pool! Stranded on his paradise island, they've no choice but to get to know each other again. But the happy girl he once knew is now a strong, gorgeous and guarded woman. Can Cade convince Reese to trust him with the traumatic secret that once ripped them apart?